Scaling Social Impact: Strategies for Spreading Social Innovations | CASE - Dees, J. Gregory; Battle Anderson, Beth; Wei-Skillern, Jane (2004)
How can social entrepreneurs effectively scale their impact to reach the many people and communities that could benefit from their innovations? As policy expert and author Lisbeth Schorr observed: “We have learned to create the small exceptions that can change the lives of hundreds. But we have not learned how to make the exceptions the rule to change the lives of millions.” If we are serious about tackling social problems on a large scale, we need to develop more effective tools to address this challenge.